Protocorm-like bodies and plant regeneration from foliar explants of Coelogyne flaccida, a horticulturally and medicinally important endangered orchid of Eastern Himalaya - De, Kaylan K. (Universidad de Costa Rica, 2015)
An efficient induction of protocrom-like bodies (PLBs) and plantlet regeneration from the young leaves of in vitro grown seedlings of Coelogyne flaccida, an horticulturally and medicinally important endangered epiphytic orchid, was accomplished in order to develop mass-scale propagation. The young leaves (1.5 cm in length) from 110 days old aseptically germinated seedling were grown in vitro in Murashige and Skoog’s (MS) medium supplemented with different concentrations and combinations of NAA ( 0.5-2 mg/L), BAP (0.5-2 mg/L) and Kn ( 0.5-2 mg/L ). The explants produced protocorm-like bodies directly from the epidermal cells of leaf without the formation of intervening callus tissue within four weeks of culture. The highest number of plantlets regenerated through PLBs per explant after 15 weeks was 35-36 in presence of NAA (2mg/l) and Kn (2mg/l). Within 20-25 weeks individual plantlets produced 2-3 leaves and 2-3 roots. Chromosome number from all plants regenerated from leaf explants showed the same chromosome number as the mother plant as 2n = 40. During acclimatization, 80% of the plantlets survived after one month of transplantation.